Integration analysis of microRNAs as potential biomarkers in early-stage lung adenocarcinoma: the diagnostic and therapeutic significance of miR-183-3p - Huang, Guodong; Liu, Yuxia; Li, Lisha; Li, Bing; Jiang, Ting; Cao, Yufeng; Yang, Xiaoping; Liu, Xinning; Qu, Honglin; Li, Shitao; Zheng, Xin (Frontiers in Oncology, 2024)
IntroductionLung adenocarcinoma (LUAD) poses a significant therapeutic challenge, primarily due to delayed diagnosis and the limited efficacy of existing treatments.MethodsTo understand the pathogenesis and identify diagnostic biomarkers for LUAD in the early stage, we investigated differential miRNA expression in 33 stage I LUAD patients between tumor and matched paracancerous tissues by Illumina Sequencing. Target genes of differentially expressed miRNAs were predicted using TargetScan and miRDB databases and further analyzed by GO and KEGG pathway enrichment analysis. The miRNAs expression results were verified using qRT-PCR. Additionally, we evaluated the clinical significance of miRNAs by the TCGA database. miR-183-3p was chosen for subsequent biological functional studies by cell proliferation assays, cell migration and cell invasion assays, cell apoptosis and cell cycle assays in LUAD cells. The clinical relevance target genes of miR-183-3p were predicted by TargetScan databases and bioinformatics assays. Gene-specific experimental validation was performed using qRT-PCR, western blotting and luciferase reporter assays.ResultsWe identified 36 differentially expressed miRNAs between LUAD tissues and matched paracancerous tissues. Target genes for these miRNAs revealed associations with processes and pathways such as RNA biosynthesis, intracellular signaling, protein transport, and the Ras, MAPK, and PI3K-AKT pathways. The qRT-PCR results were in alignment with the sequencing data for 19 out of these 21 miRNAs which not yet implicated in LUAD, 13 were up-regulated, 6 were down-regulated. The clinical relevance assays showed that 5 up-regulated miRNAs have diagnostic value for LUAD. miR-183-3p showed significant advantages in the result of sequencing, qRT-PCR, and clinical relevance assay. Biological functional assays showed that miR-183-3p emerged as a key regulator, promoting LUAD cell proliferation, decreasing apoptosis, and augmenting migration and invasion capabilities. The clinical relevance assays and experimental validation showed SESN1 as a clinical significance target of miR-183-3p.DiscussionOur study lays the foundation for investigating miRNAs with diagnostic significance in early-stage LUAD, pointing out that inhibition of miR-183-3p may serve as a novel therapeutic in LUAD.